Science and Social Innovation in the Peruvian Amazon From the Perspective and Experiences of the Urku Center - Vecco Giove, Daniel (2021)
From a summary account of the problem and the various values ​​that emerge in the department of San Martin, a transitional location between the high and lowlands of Peruvian Amazon, we describe the conditions and motivations to create Urku Estudios Amazonicos association and the pilot program Urku Center two decades ago. Thanks to the Incagro agricultural innovation program, we could team up with researchers who helped us overcome certain training limitations and approaches while providing scientific and technical support to local societies to advocate for nature conservation and indigenous rights. After the tragic events of June 2009 in the Devil's Curve, the demands of indigenous peoples received unusual support and, with this, new leaderships emerged, and particularly the organization Fekihd, in alliance with Urku, applied an innovative strategy of integral development and conservation of ancestral territories, along with the creation of economic organizations, including the Ampik Sacha association, the Maray Sisa company, and the Mushuk Runa agricultural cooperative. The inconsistency of regional policies and the influence of local powers determined limitations in the processes undertaken. At the same time, in the Urku Center, we adjusted our objectives to raise awareness among the thousands of users we received each year to promote fairer societies in harmony with nature. Our institutional experience shows how the local groups with scientific and technical capacity can contribute to resolving conflicts or advancing social demands, transferring the power of reason and jurisprudence on environmental and social issues. By decolonizing knowledge, we bring science as a product and method to the peoples who contribute much to the future's gestation and construction.